Musabaqah Syarh Alquran as Islamic Da’wah and Value Transformation - Muhammad Agung Permana; Mardian Idris Harahap (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study aims to analyze the shift in da’wah values within Musabaqah Syarh Alquran and to redefine its role as a medium for conveying Quranic messages. Ideally, syarh Quran should not only be regarded as a competition branch within Musabaqah Tilawatil Quran but also as a da’wah art that integrates rhetoric, linguistic aesthetics, and comprehension of Quranic content. This research employs a qualitative method with a tafsir-based approach. Data were collected through in-depth interviews with judges and participants at provincial and national levels, supported by observation, documentation, and literature review. Content analysis was applied to identify meaning patterns from field findings and relevant sources. The results reveal a shift in orientation from da’wah to competition, prizes, and self-expression. Nevertheless, this transformation has not eliminated its da’wah function, as syarh Quran still holds significant potential in promoting Quranic values. The study highlights the importance of strengthening coaching, establishing standardized assessment criteria, and internalizing social, religious, and cultural values in the practice of syarh Quran.